Effect Of Workload And Work Environment On Employee Work Productivity Cv. Zharry Home Creative - Nurohma , Dita; Barlian , Barin; Rahwana , Kusuma Agdhi (Universitas Dehasen Bengkulu, 2023)
PThis study aims to determine the effect of workload and work environment on the work productivity of employess CV. Zharry Home Creative. The method used is a quantitative approach with a sample of 73 respondents from employees of CV. Zharry Home Creative. The data used are primary and secondary data. The analytical tool used in this study was multiple linear regression analysis using SPSS version 25. The results showed that simultaneously workload and work environment had a significant effect on employee productivity. Partially, workload has a significant effect on employee work productivity. Partially employee work environment on employee work productivity.